Detection of JAK2V617F tyrosine kinase mutation and estimation of serum erythropoietin in blood donors who have high hematocrit - AL-Rubaie, Haythem A.; Khudeir, May A.; Al-Bayaa, Israa M (Journal of the Faculty of Medicine Baghdad, 2015)
Background: JAK2V617F mutation is the most prevalent molecular abnormality in myeloproliferative neoplasms (MPNs) and has become a valuable marker for diagnosis of MPNs. Almost all patients with polycythemia vera (PV) have this acquired mutation. However, it has also been found in many other hematological diseases, and some studies even detected the presence of JAK2V617F in normal blood samples. Objectives: To discuss the actual need to defer blood donors with high hematocrit. Patients and methods: This prospective case control study was started on 16th of December 2012 and completed on 8th of July 2013, and enrolled 94 male blood donors who attended the National Blood Transfusion Center (NBTC) in Baghdad, Iraq. Their age range was between 21 and 62 years, and their hematocrit was ≥ 0.48 l/l. A control group of 20 patients known to have JAK2V617F positive PV were also included. The following investigations were done for both the study and the control groups: complete blood count, serum erythropoietin, and real time PCR for JAK2V617F detection. Results: The present study found that 21.3% (20/ 94) of healthy blood donors were positive for JAK2V617F mutation. The mutant ratio was higher in the PV control than positive JAK2V617F donors (p=0.001). Out of 20 donors who have positive JAK2V617F mutation, 90% were smokers, and 22.8% (18/79) of all smokers were positive for JAK2V617F, while 13.3% (2/15) of non-smokers showed positivity for the mutation, the difference between various types of smoking and the level of JAK2V617F mutation among study groups was statistically insignificant with a p-value of 0.356. There is a frequent association of pruritis with JAK2 positivity as the percentage of pruritis in JAK2V617F positive blood donors was 40%. There was significant statistical difference between donors with positive JAK2V617F mutation and the PV control group for the hematocrit, total WBC count, absolute neutrophil count, and platelet count with p-values of (0.002), (0.001), (0.001), and (0.001) respectively. Conclusion: The frequency of JAK2V617F mutation was much higher than that anticipated for blood donors. The blood donated from individuals with upper normal hematocrit does not necessarily denote to complete safety of blood as being devoid of JAK2V617F mutation.